Social Forestry in Uttar Pradesh, India- History, Concept, Scheme, Objectives and Role - Husain, Mohit; Husain, Kamil; Khan, Amisher; Akhtar, Suhaiv (Indian Forester, 2018)
This review paper discusses the history, concepts, scheme and role of social forestry from local and international perspectives. It summarizes the activities of social forestry in the Uttar Pradesh, focusing on the experience and lessons learned from many bilateral and multilateral development projects involved in social forestry in the State. The programmes of most of these projects involve complex institutional development activities, technological improvement, development of infrastructure and other services to attract and retain skilled workers. Joint forest resource management and forest management planning in the state has been reviewed, in spite of the protection measures and patrolling system within natural forest reserves, dependent communities continued to extract their ever-increasing needs from the available natural resources. The paper reviews the social, ecological and economic benefits from social forestry application. The role of different organizations involved in social forestry in the state is highlighted, their involvement ranges from raising local awareness to the encouragement of participation in forest establishment, protection and management.The various varieties of Rosewood, Neem, Cassia, Gulmohar, Jakranda, Cirrus, Kanji, Mango, Chitwan, Banyan, Pipal, Ficus, Mulsri, Bauhinia, Kadamb, Tamarind, Bel and Mahua are being planted in the state as per soil and climatic conditions. The state government is emphasizing on more and more plantation of large and conventional trees.